2016
DOI: 10.5380/ce.v21i5.45455
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos De Usuários De Uma Clínica Cirúrgica Sobre a Ocorrência De Incidentes

Abstract: RESUMO:A investigação objetivou identificar a ocorrência de incidentes percebidos pelos pacientes durante o período de internação hospitalar, analisar a opinião dos usuários sobre a ocorrência de incidentes e classificar os incidentes percebidos quanto ao tipo, causas e consequências. Estudo descritivo, transversal realizado por meio de entrevistas com 80 pacientes internados na clínica cirúrgica de um hospital de ensino, no ano de 2014, norteada por um instrumento validado. A exposição ao incidente foi perceb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 14 publications
0
19
0
9
Order By: Relevance
“…As for study design, it was observed that most of the articles (37.9%) used mixed methods 15,16,17,18,19,20,21,22,23,24,25 and the same proportion (31%) adopted qualitative 26,27,28,29,30,31,32,33,34 and quantitative approaches 19,35,36,37,38,39,40,41 . There was variation in sample size and type according to quantitative and/or qualitative design.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for study design, it was observed that most of the articles (37.9%) used mixed methods 15,16,17,18,19,20,21,22,23,24,25 and the same proportion (31%) adopted qualitative 26,27,28,29,30,31,32,33,34 and quantitative approaches 19,35,36,37,38,39,40,41 . There was variation in sample size and type according to quantitative and/or qualitative design.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were performed with patients after 16,19,21,23,24,25,26,29,33,38,41,42,43 and during hospitalization 15,18,20,22,27,31,32,36,37,39,40 . Three studies used notification systems of incidents and adverse events for patients 17,28,35 In two studies 30,34 the time of data collection was not informed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations